Probing Endoplasmic Reticulum Dynamics using Fluorescence Imaging and Photobleaching Techniques - Costantini, Lindsey (2013)
This UNIT describes approaches and tools for studying the dynamics and organization of endoplasmic reticulum (ER) membranes and proteins in living cells using commercially available widefield and confocal laser scanning microscopes (CLSM). It has been long appreciated that the ER plays a number of key roles in secretory protein biogenesis, calcium regulation, and lipid synthesis. However, study of these processes has been often restricted to biochemical assays that average the behaviors of millions of lysed cells or to imaging static fixed cells. Now, with new fluorescent protein reporter tools, highly sensitive commercial microscopes, and photobleaching techniques, it is possible to interrogate the behaviors of ER proteins, membranes, and stress pathways in single cells with exquisite spatial and temporal resolution. The ER presents a unique set of imaging challenges including the high mobility of ER membranes, a diverse range of dynamic ER structures, and the influence of post-translational modifications on fluorescent protein reporters. Solutions to these challenges are described and considerations for performing photobleaching assays, especially Fluorescence Recovery after Photobleaching (FRAP) and Fluorescence Loss in Photobleaching (FLIP) for ER proteins will be discussed. In addition, ER reporters and ER-specific pharmacologic compounds are presented with a focus on misfolded secretory protein stress and the Unfolded Protein Response (UPR).